Peran Guru Dalam Mengorganisasikan Kelas Inklusif di SLB ABC Melati Aisyiyah - Hakim, Arif Rahman; Amanda, Della Latifah; Priska, Priska; Ritonga, Syahila Nazua (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Inclusive education is basically an effort to meet the educational needs of all children with a focus on vulnerable groups of marginalization. With inclusive education, it is hoped that education for all children can be implemented not just as a slogan but can really protect all children without exception. The method used in writing this journal is the qualitative method. The descriptive data obtained is in the form of words, descriptions, and behaviors expressed in the form of reports. The role of teachers in forming inclusive classes in Special Schools (SLB). As an educator, the role of teachers is critical in shaping inclusive classrooms that provide quality and supportive education for all students, including those with special needs.